Collagenolytic Activity of Some Marine Bacteria - Merkel, Joseph R. (1975)
Reconstituted, acid-extracted collagen was used to prepare a medium to screen proteolytic marine bacteria for their ability to elaborate collagenolytic enzymes. The medium was resistant to solubilization by trypsin, hyaluronidase, chondroitinase ABC, and various marine proteinases, but was readily hydrolyzed by commercial Clostridium collagenases. Eighty-seven marine isolates collected in the vicinity of Bermuda, Oahu (Hawaii), and Stone Harbor and Cape May, N.J., were screened. Approximately 44% of the isolates were capable of elaborating enzymes that hydrolyzed reconstituted collagen gels. Several cultures produced collagenolytic enzymes only when grown in the presence of collagen or degradation products of collagen, and with very few exceptions the presence of collagen in the medium greatly enhanced collagenolytic enzyme production. The enzymes from a collagenolytic Bermuda marine isolate were studied in more detail to illustrate that the enzymes capable of hydrolyzing reconstituted collagen were separable from nonspecific proteinases by zone electrophoresis and that these enzymes were true collagenases by virtue of their ability to hydrolyze native bovine Achilles' tendon obtained from three different sources.